Clinical and laboratory description of a series of cases of acute viral myositis - Silvana Paula Cardin (Jornal de Pediatria, 2015)
ABSTRACT OBJECTIVE: Describe the clinical and laboratory profile, follow-up, and outcome of a series of cases of acute viral myositis. METHOD: A retrospective analysis of suspected cases under observation in the emergency department was performed, including outpatient follow-up with the recording of respiratory infection and musculoskeletal symptoms, measurement of muscle enzymes, creatine phosphokinase (CPK), lactate dehydrogenase (LDH), transaminases (AST and ALT), blood count, C-reactive protein, and erythrocyte sedimentation rate in the acute phase and during follow-up until normalization. RESULTS: Between 2000 and 2009, 42 suspected cases were identified and 35 (27 boys) were included. The median age was 7 years and the diagnosis was reported in 89% in the first emergency visit. The observed respiratory symptoms were cough (31%), rhinorrhea (23%), and fever (63%), with a mean duration of 4.3 days. Musculoskeletal symptoms were localized pain in the calves (80%), limited ambulation (57%), gait abnormality (40%), and muscle weakness in the lower limbs (71%), with a mean duration of 3.6 days. There was significant increase in CPK enzymes (5507 ± 9180 U/L), LDH (827 ± 598 U/L), and AST (199 ± 245 U/L), with a tendency to leukopenia (4590 ± 1420) leukocytes/mm3. The complete recovery of laboratory parameters was observed in 30 days (median), and laboratory and clinical recurrence was documented in one case after 10 months. CONCLUSION: Typical symptoms with increased muscle enzymes after diagnosis of influenza and self-limited course of the disease were the clues to the diagnosis. The increase in muscle enzymes indicate transient myotropic activity related to seasonal influenza, which should be considered, regardless of the viral identification, possibly associated with influenza virus or other respiratory viruses.